Human geography an essential introduction - Boyle, Mark (Wiley-Blackwell, 2021)
Drawing on nearly three decades of instructional experience and a wealth of testing pedagogical innovations with students, Mark Boyle has revised and expanded this authoritative and comprehensive introduction to Human Geography. As with the First Edition, Boyle follows the premise that "history makes geography whilst geography makes history," and that the key to studying the principal demographic, social, political, economic, cultural and environmental processes in any region in the world today is to look at how that region has been impacted by, and in turn has impacted, the story of the rise, reign, and decline of the West. Moreover he argues that Human Geography itself is best understood as both an intellectual endeavour and a historical, political, and institutional project. Informed by recent developments in post-colonial scholarship, the book covers key concepts, seminal thinkers, and influential texts in the field. Although designed for the beginner student, Boyle does not shy away from ideas and debates often avoided in introductory texts, clearly communicating theory without condescension. In addition, he places human geography in its larger academic context, discussing the influences on the field from related subjects.